On the sedimentological origin of downcore variations of bulk sedimentary nitrogen isotope ratios - Kienast, M.; Higginson, M. J.; Mollenhauer, G.; Eglinton, T. I.; Chen, M. T.; Calvert, S. E. (Paleoceanography, 2005)
The bulk sedimentary nitrogen isotopic composition of two cores from nearby sites on the northern slope of the South China Sea (Site 17940 and Ocean Drilling Program (ODP) Site 1144) differs by up to >2‰ during the last glacial period. Given their close proximity, both core sites are located in the same biogeographic zone and nutrient regime, and it is thus unlikely that this offset is due to a true gradient in surface ocean conditions. In an attempt to resolve this offset, we have investigated the possible effects of two sedimentological parameters that can affect bulk sedimentary δ15N, namely, the variable contribution of inorganic N to bulk N in the sediment and the grain-size dependence of bulk δ15N. We find that neither effect, singly or in combination, is sufficient to explain the significant δ15N offset between the two down-core records. By elimination the most likely explanation for the observed discrepancy is a different origin of both the organic and inorganic nitrogen at each site. This study adds to the growing body of evidence highlighting the complex nature and origin of the sedimentary components in sediment drifts, such as ODP Site 1144.
id: 1066